Rank 4 Nichols Algebras of Pale Braidings - Andruskiewitsch, Nicolas (2023)
We classify finite GK-dimensional Nichols algebras B(V ) of rank 4 such that V arises as a Yetter–Drinfeld module over an abelian group but it is not a direct sum of points and blocks.